Filing for Moral Bankruptcy: An Examination of How Affect and Empathy Predict Moral Competence - Surdel, Nicholas; Klimenko, Marina A. (ETHICS IN PROGRESS, 2019)
What does being moral mean? On one hand people may justify mercy killing as sparing omeone’s suffering, but on the other hand they are still, in-fact, taking another’s life. According to Lind’s theory of moral competence (2008), it is based on consistent utilization of moral principles. Although common sense tells us that people’s affective states and levels of empathy may explain the differences, there is little direct evidence. The purpose of this study was to fill this gap by examining the relative contribution of empathy and affective state to moral competence. Results of the study revealed that although perspective taking and negative affective state were both significant predictors of moral competence, perspective taking was a stronger contributor. This suggests that the next time you deliberate over a moral dilemma (e.g., euthanasia), you should try understanding another person’s perspective rather than feeling empathy to make the best moral judgment.